2020
DOI: 10.3389/fnins.2020.560668
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Vagus Nerve Stimulation Effects on Rat Cardiovascular and Immune Systems

Abstract: Background: Investigations into the benefits of vagus nerve stimulation (VNS) through pre-clinical and clinical research have led to promising findings for treating several disorders. Despite proven effectiveness of VNS on conditions such as epilepsy and depression, understanding of off-target effects and contributing factors such as sex differences can be beneficial to optimize therapy design. New Methods: In this article, we assessed longitudinal effects of VNS on cardiovascular and immune systems, and studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…Additionally, contrary to the fact that females have higher HR than males, both in humans and mice (Prabhavathi et al, 2014 ; Yang et al, 2007 ), our study showed the opposite phenomena across control and pancreatic liver groups. This is a curious discrepancy since several studies have reported in humans and conscious rats that healthy females have higher parasympathetic activity than males, which agrees with our findings (Korotkov, 2017 ; Yaghouby et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, contrary to the fact that females have higher HR than males, both in humans and mice (Prabhavathi et al, 2014 ; Yang et al, 2007 ), our study showed the opposite phenomena across control and pancreatic liver groups. This is a curious discrepancy since several studies have reported in humans and conscious rats that healthy females have higher parasympathetic activity than males, which agrees with our findings (Korotkov, 2017 ; Yaghouby et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, clinical VNS paradigms for migraine patients do not differ between genders. Furthermore, except for cardiac activity, no significant correlation between gender and VNS efficacy on neuronal activity or inflammation has been reported in literature [ 3 , 58 , 59 ]. Second, together with our prior work, nVNS delivered at 20-40 min before CSD susceptibility testing exhibits suppressive effect on CSD, suggesting that VNS efficacy begin at 20-40 min.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, there were studies reporting the sex differences in hemodynamic and autonomic regulation of cardiovascular systems both on animal and human trials. [36,37] In terms of adverse effects of VNS, female subjects were more likely to express side effects than that of males, and this difference may originate from discrepancy in the sensitivity of certain nuclei following the cardiac branch pathway in female and male subjects. [38,39] On the difference of the curative effects of VNS, female subjects also performed less effectiveness.…”
Section: Discussionmentioning
confidence: 99%